Distribution, characteristics, metallogenic processes and prospecting potential of terrestrial brine-type lithium deposits in the world and lithium demand situation - Dian-he Liu; Cheng-lin Liu; Chun-lian Wang; Xiao-can Yu (China Geology, 2025)
ABSTRACT: In response to the rise of the energy storage industries such as new energy vehicles and the wide application of lithium in various fields worldwide, the global demand for lithium resources has been in explosive growth. In order to further comprehensively understand the global supply and demand pattern, development and utilization status, genesis of ore deposits and other characteristics of lithium resources, based on the achievements of many researchers at home and abroad, this paper systematically summarized the lithium supply and demand situation, resource endowment, deposit classification and distribution, typical geological characteristics, metallogenic factors and metallogenic regularity of terrestrial brine-type lithium deposits which are the main types of development and utilization all over the world. The review shows that brine-type lithium resource and (or) reserves in the plateau salt lakes are huge and play an important role. In addition, the mineralization potential of the underground brine-type lithium deposit is broad worldwide. The potential resources of underground brines are enormous, and the geothermal spring water type is also worthy of attention. Brine lithium deposits are mainly controlled by the subduction and collision of regional plate tectonics, arid climate and provenance conditions. Strengthening of the scientific research on underground brines in the future is expected to provide another significant support for the global demand for lithium resources.